Interactions between the Cyclooxygenase Metabolic Pathway and the Renin-Angiotensin-Aldosterone Systems: Their Effect on Cardiovascular Risk, from Theory to the Clinical Practice - Mochol, Jakub; Derkacz, Arkadiusz; Szahidewicz-Krupska, E.; Gawrys, Karolina; Gawrys, Jakub; Doroszko, A. (BioMed research international, 2018)
Coronary artery disease (CAD) and stroke are the most common and serious long-term complications of hypertension. Acetylsalicylic acid (ASA) significantly reduces their incidence and cardiovascular mortality. The RAAS activation plays an important role in pathogenesis of CVD, resulting in increased vascular resistance, proliferation of vascular-smooth-muscle-cells, and cardiac hypertrophy. Drugs acting on the renin-angiotensin-aldosterone system (RAAS) are demonstrated to reduce cardiovascular events in population with cardiovascular disease (CVD). The cyclooxygenase inhibitors limit the beneficial effect of RAAS-inhibitors, which in turn may be important in subjects with hypertension, CAD, and congestive heart failure. These observations apply to most of nonsteroidal anti-inflammatory drugs and ASA at high doses. Nevertheless, there is no strong evidence confirming presence of similar effects of cardioprotective ASA doses. The benefit of combined therapy with low-doses of ASA is—in some cases—significantly higher than that of monotherapy. So far, the significance of ASA in optimizing the pharmacotherapy remains not fully established. A better understanding of its influence on the particular CVD should contribute to more precise identification of patients in whom benefits of ASA outweigh the complication risk. This brief review summarizes the data regarding usefulness and safety of the ASA combination with drugs acting directly on the RAAS.